2003
DOI: 10.1002/cne.10539
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the primary motor cortex connections with the thalamus in primates

Abstract: Six injections (approximately 1 mm in diameter) of biotinylated dextran amine (BDA) were placed in different locations of the primary motor cortex of the rhesus monkey. Anterograde and retrograde labeling patterns in the thalamus were charted and individual labeled axons traced in continuous serial sections. Both anterograde and retrograde labeling in the thalamus was extensive, spanning several millimeters mediolaterally and including ventral lateral, ventral anterior, centromedian, and centrolateral nuclei. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 75 publications
9
64
0
Order By: Relevance
“…The complex somatotopographic pattern of selective divergence and convergence in the projections of the DCbN revealed by the present data fits well with the general pattern of organization at many levels of the motor pathway (e.g., Shambes et al, 1978;Anderson and Turner, 1991;Schieber and Hibbard, 1993), including even the pattern of divergence and convergence in the innervation of peripheral motor units by spinal motorneurons (e.g., Sugiuchi et al, 2004). Furthermore, similar to the present findings, other studies have revealed that comingled neurons within particular portions of the motor system project selectively to different targets but are rarely double-labeled (Darian-Smith et al, 1990;Akintunde and Buxton, 1992;Tokuno and Tanji, 1993;Stepniewska et al, 1994;Rouiller et al, 1999;Morel et al, 2005; see also Kultas-Ilinsky et al, 2003). The repeated theme of selective projections within a complex pattern of …”
Section: Figure 10 (Continued)supporting
confidence: 88%
“…The complex somatotopographic pattern of selective divergence and convergence in the projections of the DCbN revealed by the present data fits well with the general pattern of organization at many levels of the motor pathway (e.g., Shambes et al, 1978;Anderson and Turner, 1991;Schieber and Hibbard, 1993), including even the pattern of divergence and convergence in the innervation of peripheral motor units by spinal motorneurons (e.g., Sugiuchi et al, 2004). Furthermore, similar to the present findings, other studies have revealed that comingled neurons within particular portions of the motor system project selectively to different targets but are rarely double-labeled (Darian-Smith et al, 1990;Akintunde and Buxton, 1992;Tokuno and Tanji, 1993;Stepniewska et al, 1994;Rouiller et al, 1999;Morel et al, 2005; see also Kultas-Ilinsky et al, 2003). The repeated theme of selective projections within a complex pattern of …”
Section: Figure 10 (Continued)supporting
confidence: 88%
“…However, this statement should be taken as applicable only to the markers analyzed in this study, because physiological and pathway tracing studies imply that certain compartmentalization may exist within VL as well (Asanuma et al, 1983;Mackel et al, 1992;Kultas-Ilinsky et al, 2003).…”
Section: Local Circuit Neurons and Their Connectivitymentioning
confidence: 93%
“…As noted above, VP receives cutaneous input. The VPs, however, processes inputs from deep receptors of the skin and joints (e.g., Asanuma et al, 1983; e.g., Dykes et al, 1981;Friedman and Jones, 1981;Kaas et al, 1984), and VL is associated with the motor system (Asanuma et al, 1983;Gonzalo-Ruiz and Leichnetz, 1990;Ilinsky and Kultas-Ilinsky, 2002;Kultas-Ilinsky et al, 2003;Stepniewska et al, 1994b;Vitek et al, 1994;Vitek et al, 1996). The anterior pulvinar is a nucleus associated with somatic processing (e.g., Asanuma et al, 1985;Cusick and Gould, 1990; see Grieve et al, 2000 for review;Jones et al, 1979;Pons and Kaas, 1985).…”
Section: Thalamocortical Connections Of Anterior Parietal Areas 3b Anmentioning
confidence: 97%